Cash Waqf Linked Green Sukuk: Analisis Multiakad dalam Perspektif Fikih Muamalah - Qanita, Ariza (Universitas Negeri Surabaya, 2023)
This research aims to examine the sharia legal aspects of cash waqf linked green sukuk from the perspective of fiqh muamalah. Cash waqf linked green sukuk is an innovative form of integration between cash waqf and green sukuk. This instrument has great potential for sustainable economic empowerment. However, in practice, cash waqf linked green sukuk used a hybrid contract that combines Islamic commercial finance and Islamic social finance, so studies regarding its validity are needed. This research used qualitative methods with a normative juridical approach. The research results showed that hybrid contracts in cash waqf linked green sukuk are permitted for several reasons. First, the rule that the basic law of all forms of muamalah is permissible as long as there is no argument (nash) that forbids it. Second, cash waqf and green sukuk are both sharia-based instruments. Third, the integration of cash waqf and green sukuk does not eliminate the substance of waqf to create social welfare for the community. Fourth, cash waqf linked green sukuk encourages more optimal use of funds. Fifth, the transaction is in accordance with the demands of current developments. Sixth, cash waqf linked green sukuk contributes to maintaining a sustainable environment.